"Taste the Difference": The Children's Book for Boys and The Children's Book for Girls in Boris Akunin's "Genres" Project. (2nd April 2016) - Savkina, Irina
Abstract : The article compares two texts that were published as part of Boris Akunin's "Genres" project from a gender perspective: The Children's Book for Boys and The Children's Book for Girls . The author concludes that the books reproduce traditional notions of masculinity and particularly femininity. The girl target audience of the book is invited to self-identify with some universal, essentialist model of femininity, which reproduced patriarchal gender stereotypes.